Hypothesis: Taurine therapy of nephropathic cystinosis may correct the deficiencies of cysteamine therapy - Jess G. Thoene (Molecular Genetics and Metabolism Reports)
Untreated nephropathic cystinosis is a lethal autosomal recessive disease. The current specific therapy, cysteamine, ameliorates the renal function loss, but does not alter the renal Fanconi syndrome, short stature, muscle weakness, male infertility, and other concerns. The primary biochemical/physiological defect in cystinosis is failure to supply cysteine to mTOR via cystinosin. This leads mTOR to react in starvation mode, which stops cell differentiation, leading to proximal tubule loss, and ultimately renal failure. It also increases apoptosis and autophagocytosis rates, which may contribute to impaired growth. Many of the defects which occur in cystinosis are corrected by taurine in other conditions as described. Cystinosis patients have been shown to be severely deficient in plasma taurine. Although use of taurine is not yet reported in cystinosis in vitro or in vivo, given the safety of taurine, its deficiency in cystinosis, and its potency in correcting similar defects in other conditions, it appears reasonable to engage in a clinical trial of taurine in nephropathic cystinosis.